2013
DOI: 10.1095/biolreprod.113.108100
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Inhibitor of the Gamma-Secretase Complex on Proliferation and Apoptotic Parameters in a FOXL2-Mutated Granulosa Tumor Cell Line (KGN)1

Abstract: Ovarian granulosa cell tumors (GCTs) represent 3%-5% of all ovarian malignancies. Treatments have limited proven efficacy and biologically targeted treatment is lacking. The aim of this study was to investigate the role of Notch signaling in the proliferation, steroidogenesis, apoptosis, and phosphatidylinositol 3-kinase (PI3K)/AKT pathway in a FOXL2-mutated granulosa tumor cell line (KGN) representative of the adult form of GCTs. When Notch signaling is initiated, the receptors expose a cleavage site in the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…More recently, Wang et al (2011) have reported that in prostate cancer cells, the downregulation of NOTCH1 leads to the inhibition of cell growth mechanistically linked with the downregulation of AKT, suggesting that this protein is a downstream target of Notch1 signaling. In addition, in a previous work we have demonstrated that phosphorylation of AKT is repressed in a granulosa cell line (KGN) cultured with a Notch inhibitor (Irusta et al 2013). In this study, we showed that phosphorylation of AKT was inhibited in CL treated with DAPT and that this effect was reversed with coincubation with progesterone.…”
Section: Link Between Notch and Progesterone In CL Functionsupporting
confidence: 53%
See 1 more Smart Citation
“…More recently, Wang et al (2011) have reported that in prostate cancer cells, the downregulation of NOTCH1 leads to the inhibition of cell growth mechanistically linked with the downregulation of AKT, suggesting that this protein is a downstream target of Notch1 signaling. In addition, in a previous work we have demonstrated that phosphorylation of AKT is repressed in a granulosa cell line (KGN) cultured with a Notch inhibitor (Irusta et al 2013). In this study, we showed that phosphorylation of AKT was inhibited in CL treated with DAPT and that this effect was reversed with coincubation with progesterone.…”
Section: Link Between Notch and Progesterone In CL Functionsupporting
confidence: 53%
“…In addition, different reports have demonstrated the interaction between the Notch signaling and PI3K/ AKT pathways in cancer cells (Meurette et al 2009, Wang et al 2011. In this context, we have recently demonstrated that Notch induces granulosa cell tumor proliferation, decreases apoptosis-mediated cell death, and might be interacting with the PI3K/AKT signaling pathway (Irusta et al 2013). Yet, the cellular mechanisms by which progesterone exerts its local effects and whether progesterone interacts with the Notch system in CL survival remain incompletely understood.…”
Section: Introductionmentioning
confidence: 90%
“…First, we detected cell growth and cell apoptosis in cells treated with DAPT only or in those treated with DAPT followed by t-AUCB. Because DAPT itself can also inhibit cell growth at certain concentrations and to avoid this effect, we applied DAPT at a low concentration of 2 μmol/L, which was demonstrated by others [19][20][21][22] and our current study have no significant effects on cell growth inhibition or cell apoptosis induction. Our results showed that with the pre-treatment of DAPT, cell growth inhibition in t-AUCB-treated U251 and U87 glioblastoma cells was strengthened significantly.…”
Section: Discussionmentioning
confidence: 56%
“…FOXO1/3 (forkhead box O1/3) also inhibited SMAD3 [ 12 ]. The interaction between Notch signaling and PI3K/AKT were also proved [ 13 ]. In the following sections, we will summarize the influence of different cell signaling network on GCT.…”
Section: Introductionmentioning
confidence: 99%